Pengembangan Media Pembelajaran Berbasis Software Geogebra pada Kubus untuk Mengembangkan Kemampuan Spasial Siswa - Sigit Raharjo; Astrino Purmanna; Kus Andini Purbaningrum; Riche Ramayanti; Dea Mei Cahya Muhti (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2023)
The development of science and technology affects the emergence of interactive learning media. Interactive learning media is expected to be able to foster students’ learning motivation and spatial abilities. This study aimed to develop learning media based on geogebra software on cubes to deveop students’ spatial ability. This study applies the ADDIE model (analysis, design, development implementation, evaluation) as a research and development model for creating interactive learning media using geogebra on cube theory. Tha sample in this study amounted to 20 students where these students had not received theory about cubes. The research data was obtained through filling out a questionnaire evaluation test for students’ responses to learning. The quality of geogebra based learning media is related to three criteria, namely validity, practicality, and effectiveness. Based on the results of the research and analysis carried out, the interactive learning media that has been developed meets good validity criteria, can be used practically in learning and is able to grow students’ spatial ability in cube theory